Upaya Menciptakan Budaya Anti Korupsi melalui Tradisi Banjar - Novitasari Novitasari (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
Corruption crimes have long occurred in Indonesia and the perpetrators are not infrequently involving various groups of societies. Whereas preventive measures have not focused much directly on civil society. Therefore, the purpose of this research is to uncover the efforts to develop an anti-corruption culture in the community through the implementation of the banjar. This study uses a qualitative approach to the case study method. Data are obtained through interviews and literature studies. Data analysis techniques use the Miles and Huberman model. The result of the study shows that the implementation of banjar is one of the community's efforts to cultivate anti-corruption values. The suggestions that the writer can give are based on the results of this study, namely: 1) Indonesian people are rich in local wisdom which contains positive values including the implementation of this banjar so that it must be preserved; 2) the cultivation of the value of anti-corruption through the implementation of banjar is an experience that can be a reference in learning in formal education in schools and universities so that it has sustainable benefits